Dissociative Symptoms and Mother's Marital Status in Young Adult Population. Issue 2 (January 2015) - Bob, Petr; Selesova, Petra; Raboch, Jiri; Kukla, Lubomir; King., Patricia
<x xml:space="preserve">Abstract</x> Abstract Current findings suggest that mother's marital status indicating father's absence or conflicting relationship to father may be specifically related to dissociation and other stress-related symptoms. We have assessed relationships of mother's marital status, dissociative symptoms, and other psychopathological manifestations in a sample of 19 years' old young adults (N = 364) participating in European longitudinal study (European Longitudinal Study of Parenthood and Childhood). The results show clinically significant manifestations of dissociative symptoms in young adult men whose mothers were fatherless and in women whose mothers were re-married. Other psychopathological symptoms did not reach clinically significant manifestations. The results suggest that significant factor related to high level of dissociative symptoms in men growing in fatherless families might be linked with disturbed and conflicting attachment to a father's figure and pathological dependent attachment to mother. In women dissociative symptoms likely are linked to conflicting relationship between mother and daughter associated with stepfather' presence in the family.